1990
DOI: 10.1136/jcp.43.12.1034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two preparatory techniques for urine cytology.

Abstract: Two methods of preparation of urine for cytology were compared retrospectively. In method 1 cells in the urine were fixed after the preparation of the smear; in method 2 the cells were fixed before smear preparation. Urine cytology reports were correlated with subsequent histological analysis. The specificities of urine cytology using both methods were high (99%). The sensitivity using method 1 was 87%; using method 2 it was 65%. This difference was significant. The cell preparation technique therefore signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…cells were used (2). After collection they were transported using IsoTherm System (Eppendorf, Germany) to the laboratory and were immediately processed for the preparation of glass-slide smears.…”
Section: Reactivation Of Polyomavirus Hominis 1 (Bk Virus Bkv) Is Anmentioning
confidence: 99%
“…cells were used (2). After collection they were transported using IsoTherm System (Eppendorf, Germany) to the laboratory and were immediately processed for the preparation of glass-slide smears.…”
Section: Reactivation Of Polyomavirus Hominis 1 (Bk Virus Bkv) Is Anmentioning
confidence: 99%
“…Previous studies have two methods of preparation of urine for cytology were compared retrospectively In method 1 cells in the urine were fixed after the preparation of the smear; in method 2 the cells were fixed before smear preparation. Cellular fixation after smear preparation is preferable to smear 3 preparation after fixation (Dhundee and Rigby, 1990). Mygind, et al in (1987) they found Espostis fixative resulted in a good preservation for cytological examination and formalaldehyde or 10% isopropanole were poorly preserved (Mygind and Lauritzen, 1987).…”
mentioning
confidence: 99%